PENGARUH KESADARAN WAJLB PAJAK TERHADAP KEPATUHAN WAJLB PAJAK DALAM MEMBAYAR PAJAK BUML DAN BANGUNAN DL KABUPATEN MLNAHASA UTARA - Bill, Makarau Jonathan; Kalangi, Lintje; Mawikere, Lidia (Universitas Sam Ratulangi, 2018)
Taxpayer compliance becomes an important behavioral pattern in relation to improve the tax revenue sector. Taxpayer compliance can be influenced by various factors, one of them is the awareness of the taxpayer. This research is intended to determine the awareness of taxpayers on compliance in paying the tax on land and building tax in North Minahasa District. This research uses quantitative method with 100 respondents. The results of this study indicate that the awareness of taxpayers influences taxpayer compliance in paying the tax on the land and building tax in North Minahasa District. The research results show significance with a probability value of 0.000 smaller than 0.05, with the result that Ho is rejected. Thus there is significant with partial influence on taxpayer awareness of compliance in paying the tax on the land and building tax, then the Ha is accepted.Keywords : Awereness of Taxpayer, Taxpayer Compliance.